Euphemism and political correctness in contemporary English - N B Rubina (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2011)
The presented article is devoted to the consideration of such linguistic category as the political correctness which was widely adopted in the English-speaking countries and made considerable impact on modern English language. Linguistic political correctness is the most curious language theme to ignore which, means to miss the major aspect of modern English language.